Significant Role Positive Leadership in Mediator of Workplace Diversity on Employee Well-Being - Iwan Prasetyo; Mariana Kristiyanti (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
This research specifically aims to analyze the influence of workplace diversity on employe well-being, analyze the impact of positive leadership on employe well-being, and analyze the mediating role of positive leadership in the relationship between workplace diversity and employe well-being. This research uses a quantitative approach with a survey design thru Google Forms involving 130 participants. The sampling technique used was purposive sampling with criteria of working in the retail sector and having a minimum of 1 year of work experience. From this research, it is explained that workplace diversity has a significant and positive direct effect on employe well-being, positive leadership has a significant positive effect employe well-being, and workplace diversity has a significant and positive effect on positive leadership. Positive leadership mediates the relationship between workplace diversity and employe well-being. The theoretical contribution of the research by expanding the study on the mechanism of positive leadership in mediating the relationship between workplace diversity and employe well-being